2021
DOI: 10.1002/ajh.26389
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency and fatigue among adolescents with bleeding disorders

Abstract: Iron deficiency anemia is associated with heavy menstrual bleeding (HMB) and, by extension, a bleeding disorder (BD). It is unknown if iron deficiency without anemia is associated with a BD in adolescents. Moreover, the threshold of ferritin associated with fatigue in adolescents with HMB is unclear. In this multicenter study, we enrolled adolescents with HMB without BD. Participants underwent BD and anemia work-up in Young Women's Hematology Clinics and completed the Peds QL™ fatigue scale. BDs were defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…We interviewed nine adolescents (median age: 17 years; range: [16][17][18] with an inherited BD, including VWD type I (n = 5), VWD type 2B (n = 2), VWD type 3 (n = 1), and inherited thrombocytopenia (n = 1; Table 1). The median Pictorial Bleeding Assessment Chart score was 465 (range 250-840), and the median ISTH-BAT score was 5 (range [3][4][5][6][7][8][9][10][11]. All participants were on hormonal menstrual suppression (n = 9) and as-needed antifibrinolytics (n = 7).…”
Section: Re Sultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We interviewed nine adolescents (median age: 17 years; range: [16][17][18] with an inherited BD, including VWD type I (n = 5), VWD type 2B (n = 2), VWD type 3 (n = 1), and inherited thrombocytopenia (n = 1; Table 1). The median Pictorial Bleeding Assessment Chart score was 465 (range 250-840), and the median ISTH-BAT score was 5 (range [3][4][5][6][7][8][9][10][11]. All participants were on hormonal menstrual suppression (n = 9) and as-needed antifibrinolytics (n = 7).…”
Section: Re Sultsmentioning
confidence: 99%
“…[1][2][3] Heavy menstrual bleeding results in hospitalizations, iron deficiency anemia, depression, and limitations of daily activities. [4][5][6][7] Among adolescents with HMB, up to 30% are diagnosed with an underlying BD in tertiary care settings. 2,8 Bleeding disorders are treatable and their complications are preventable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from our cohort stresses the importance of screening for iron deficiency in this population and treating with iron therapy when iron deficiency (ferritin <20 ng/mL) is present 18,19 . Earlier detection and treatment prevents progression to anaemia and addresses other clinical implications of iron deficiency including poor concentration, fatigue, restless legs and decreased school performance in adolescent females 27–31 . A previous study of adolescent females admitted for severe anaemia revealed that only 39% had any iron laboratory assessment and 37% of admissions did not initiate iron therapy 32 .…”
Section: Discussionmentioning
confidence: 75%
“…18,19 Earlier detection and treatment prevents progression to anaemia and addresses other clinical implications of iron deficiency including poor concentration, fatigue, restless legs and decreased school performance in adolescent females. [27][28][29][30][31] A previous study of adolescent females admitted for severe anaemia revealed that only 39% had any iron laboratory assessment and 37% of admissions did not initiate iron therapy. 32 Screening with serum ferritin is important over a haemoglobin or complete blood count alone as less than half of adolescent females may be anaemic or microcytic.…”
Section: Discussionmentioning
confidence: 99%